Pengaruh Tata Kelola Kelembagaan dan Usaha terhadap Efektivitas Pengelolaan Hutan melalui Kinerja KTH di Perhutanan Sosial Glagalinggah, Kintamani, Bali : Pengaruh Tata Kelola Kelembagaan dan Usaha terhadap Efektivitas Pengelolaan Hutan melalui Kinerja KTH di Perhutanan Sosial Glagalinggah, Kintamani, Bali - Pasaribu, Lusi Maulina; Dewi, Ni Luh Prima Kemala (Universitas Duta Bangsa Surakarta, 2025)
Social forestry refers to a forest management approach that grants lawful access to local communities for the sustainable use and stewardship of forest resources. This initiative aims to enhance local livelihoods while ensuring long-term environmental integrity. In Glagalinggah Village, the implementation of this program encounters several challenges, particularly in institutional and business governance aspects. These limitations hinder the performance of Forest Farmer Groups (KTH), which in turn obstruct the continuity of business operations and forest rehabilitation efforts. This research investigates the influence of institutional and business governance on KTH performance and the effectiveness of social forestry management. Employing a quantitative approach with SEM-PLS analysis, data were gathered from 70 KTH members. The findings reveal that while both types of governance significantly influence KTH performance, their direct impact on forest management effectiveness is not significant, establishing KTH performance as a full mediating variable. Business governance issues such as low member participation, limited access to capital, and insufficient technological application emerge as the primary barriers. The study highlights the need to strengthen governance capacity to improve group performance and ensure sustainable forest management outcomes. These insights can support local-level policy planning for more effective social forestry programs.